Inequality, public opinion, and redistribution - Lane Kenworthy; Leslie McCall (Luxembourg Income Study (LIS), 2007)
According to the 'median-voter' hypothesis, greater inequality in the market distribution of earnings or income tends to produce greater generosity in redistributive policy. We outline the steps in the causal chain specified by the hypothesis and attempt to assess these steps empirically. Prior studies focusing on cross-country variation have found little support for the median-voter model. We examine over-time trends in eight nations during the 1980s and 1990s. Here too the median-voter hypothesis appears to have little utility.
Keywords: 330; Wahlverhalten; Verteilungsgerechtigkeit; Verteilungspolitik; Neue politische Ökonomie; Großbritannien; USA; Kanada; Australien; Italien; Deutschland; Schweden; Norwegen